Taurine Prevents Impairments in Skin Barrier Function and Dermal Collagen Synthesis Triggered by Sleep Deprivation-Induced Estrogen Circadian Rhythm Disruption - Qi Shao; Zhaoyang Wang; Yifang Li; Xun Tang; Ziyi Li; Huan Xia; Qihong Wu; Ruxue Chang; Chunna Wu; Tao Meng; Yufei Fan; Yadong Huang; et al. (Cells)
Sleep deprivation is a prevalent issue that disrupts the circadian rhythm of estrogen, particularly estradiol, thereby significantly affecting women’s skin health and appearance. These disruptions can impair skin barrier functionality and decrease dermal collagen synthesis. In this study, our results demonstrate that topical taurine supplementation promotes the expression of tight junction (TJ)-related proteins and enhances collagen production, effectively restoring skin homeostasis in sleep-deprived female mice. Mechanistically, taurine upregulates the expression of TMEM38B, a gene encoding the TRIC-B trimeric cation channel, resulting in increased intracellular calcium ion levels. This, in turn, promotes the upregulation of TJ-related proteins, such as ZO-1, occludin, and claudin-11 in epidermal cells, while also enhancing the expression of type III collagen in fibroblasts, thus restoring skin homeostasis. These findings suggest that taurine may serve as an alternative to estradiol, effectively improving skin homeostasis disrupted by sleep deprivation while mitigating the potential risks associated with exogenous estrogen supplementation. Collectively, these results provide preliminary insights into the protective mechanisms of taurine against sleep deprivation-induced skin impairments and establish a foundation for its potential application in treating skin conditions related to estrogen imbalances, such as skin aging in menopausal women.